Survey and the 7th century in the Western Argolid - Caraher, William; Gallimore, Scott; Nakassis, Dimitri; James, Sarah A. (Journal of Greek Archaeology, 2020)
The past two decades have witnessed a major change in how archaeologists understand the Late Roman and Early Medieval landscape of Greece. The rise of survey archaeology in the late-20th century fueled a growing awareness of the ‘busy countryside’ of Late Antiquity. This complemented work in urban areas across Greece and the Eastern Mediterranean more broadly by demonstrating that Late Roman cities and their countryside experienced continued prosperity, social vitality, and political and economic significance into the 5th and 6th centuries. Recent work has challenged the idea that the supposed Slavic invasions of the late-6th century brought an end to this Late Antique prosperity and initiated a period of economic, political, and social dislocation often called the ‘Dark Ages.’ This revised interpretation draws on evidence from the northeastern Peloponnese, with work at the site of Corinth, in particular, demonstrating that the city continued to prosper well into the 7th century. Imported ceramics indicate that Corinth remained connected to production sites across the Mediterranean even if these connections appear to be less dynamic and consistent than earlier centuries. The site also benefited from the intensification of regional networks from the late-6th through 7th centuries. The results from Corinth suggest that the city experienced economic change in the 7th century, but that this change was not the same as decline and indicates continuity with earlier centuries as much as new patterns of economic and social relations. This revised view of the 7th century at Corinth has pushed both excavations and intensive survey projects to think more critically about the chronology of assemblages elsewhere in Greece and the Eastern Mediterranean.